Primary Ta high grade bladder tumors: Determination of the risk of progression - Quhal, Fahad; D'Andrea, David; Soria, Francesco; Moschini, Marco; Abufaraj, Mohammad; Rouprêt, Morgan; Karakiewicz, Pierre I; Yang, Lin; Mostafaei, Hadi; Laukhtina, Ekaterina; Mori, Keiichiro; Sari Motlagh, Reza; et al. (Urologic oncology, 2021)
PURPOSE: TaG3 bladder cancer is an under-investigated disease and because of its rarity it is commonly studies together with T1G3 disease. We sought to exclusively study TaG3 disease and to determine the factors associated with disease progression. MATERIAL AND METHOD: We retrospectively studied patients with primary TaG3 bladder cancer. Progression to ≥pT1 and pT2 were analyzed using Cox and competing-risk regression analyses. RESULTS: Of 3,505 consecutive patients with nonmuscle invasive bladder cancer, 285 patients had primary TaG3 without concomitant carcinoma in-situ. Progression to ≥pT1 occurred in 21 patients (7.4%). In a multivariable competing-risk regression analysis, intravesical Bacillus Calmette-Guerin (BCG) was significantly associated with a lower risk of progression to ≥pT1 (HR 0.23, 95%CI 0.08-0.64, P = 0.005). Recurrence in the first year of diagnosis was significantly associated with an increased risk of stage progression to ≥pT1 (HR 7.81, 95%CI 2.50-24.44, P < 0.001). Progression to ≥T2 was observed in 9 patients (3.2%). In univariable competing-risk regression analyses, intravesical BCG was significantly associated with a lower risk of progression to ≥pT2 (HR 0.11, 95%CI 0.04-0.47, P = 0.003). On the other hand, recurrence in the first year of diagnosis was significantly associated with an increased risk of stage progression to ≥T2 (HR 7.12, 95%CI 1.50-33.77, P = 0.013). In a subgroup of 199 patients who were treated with BCG, there was no statistically significant association between tumor recurrence in the 1st year of diagnosis and stage progression to ≥pT1 (P = 0.14) or ≥pT2(P = 0.19). CONCLUSION: Patients with TaG3 bladder cancer are considered high risk but if appropriately treated with BCG that risk is considerably mitigated. Our data support that TaG3 without concomitant carcinoma in-situ should not be considered as aggressive as T1G3 as it has a lower risk of progression to muscle-invasive bladder cancer. Recurrence in the first year after diagnosis is the strongest predictor of progression to muscle-invasive bladder cancer.
Keywords: Disease Progression; Aged; hodnocení rizik; Retrospective Studies; lidé středního věku; senioři; nádory močového měchýře; lidé; Middle Aged; Female; Risk Assessment; Male; ženské pohlaví; Neoplasm Grading; progrese nemoci; Humans; mužské pohlaví; stupeň nádoru; Urinary Bladder Neoplasms; retrospektivní studie